GURU SEBAGAI ROLE MODEL DALAM MEMBINA SIKAP SPIRITUAL DAN SIKAP SOSIAL SISWA - Firdiansyah (LPPM STAI Haji Agus Salim, 2024)
Abstract Educators are expected to be able to guide their students to become individuals who are not only intellectually intelligent but also emotionally and spiritually intelligent. This research aims to describe teachers as role models in fostering students' spiritual and social attitudes. The research method used is descriptive qualitative research. The research participants are 10 teachers and 5 students at SMPIT Al-Mufid. The data shows that teachers, as role models, play a crucial role in shaping students' spiritual and social attitudes, including: (1) teachers as role models in teaching; (2) teachers as role models in discipline; (3) teachers as role models in cleanliness; (4) teachers as role models in worship and prayer. The research findings can serve as information for the development of the teacher's role as a role model in shaping students' attitudes in school. Keywords: Role Model, Spiritual Attitude, Social Attitude